Analisis Kesulitan Anak dalam Mengidentifikasi Simbol Angka dan Memilih Warna - Sholihat, Nita Zaskia; Sabani, Fatmaridah; Hutami, Eka Poppi; Hasis, Pertiwi Kamariah (Generasi Emas, 2025)
The difficulty some children face in recognizing numbers and choosing colors is experienced by several children at RA Bahrul Ulum Luwu Utara. This study aims to understand the description and factors causing children’s difficulties in identifying number symbols and selecting colors. The method used is qualitative with a case study approach through observation, and data collection techniques including observation and interviews. The research results show that the difficulties children face in identifying number symbols and choosing colors include difficulty understanding the shape of numbers, difficulty in ordering numbers, and difficulty in associating images with numbers. Meanwhile, the difficulties in choosing colors are confusion when asked about colors, difficulty associating colors with objects, and dependence on the teacher. The factors causing children's difficulties in identifying number symbols and colors are lack of parental attention, lack of focus and interest, dependency behavior, the negative influence of a strict teaching approach, the habit of playing with phones, and children attending school infrequently. Therefore, this study suggests that early learning for children to introduce numbers can start with lines (|) that can form numbers 1-10. For color recognition, an initial step that can be used is conducting outdoor activities by taking the children on a tour outside while observing the colors of nature, such as the colors of leaves, flowers, the sky, or surrounding objects.